The Dangerous Threat to Roe v. Wade. Issue 1 (March 2020) - Unknown
Abstract : ( N Engl J Med . 2019;381(10):979) Since the Supreme Court Roe v. Wade decision, care providers have worked hard to reduce deaths due to unsafe abortion procedures. Currently, there are no formal records keeping track of critical illness or infertility that resulted from unsafe abortions; the World Health Organization (WHO) has approximated that 22 million unsafe abortions are performed each year in areas where women cannot access safe and legal abortion services. Each unsafe procedure runs the risk of lifelong disability or death, and these results could easily be prevented with comprehensive public health services.